Inventory of assessment practices in people with profound intellectual and multiple disabilities in three European countries. Issue 6 (16th June 2021) - Wessels, Marleen D.; van der Putten, Annette A. J.; Paap, Muirne C. S.
Abstract: Background: Knowledge about the quality of assessment methods used in the support of people with profound intellectual and multiple disabilities (PIMD) is scarce. This study aimed to provide an overview of the assessment methods used in practice and to examine whether these instruments were studied for their psychometric properties for people with PIMD. Method: Professionals ( N = 148) from three European countries completed a survey on assessment practices. We performed a literature search to find information about the psychometric properties of the instruments that were identified in the survey. Results: Of the participants, 78.1% used assessments that were not developed for people with PIMD. Documentation on psychometric properties was found for 8 out of 116 instruments. Conclusions: Most of the instruments in use were not designed for people with PIMD, and information about their quality is lacking. Guidelines are needed regarding the use and development of assessment methods for people with PIMD.